Meta Analysis on The Correlation Between Listen-Read-Discuss (L-R-D) and Reading Comprehension - Raynaldo, Mickhael Tommy; Panjaitan, Nelson Balisar (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
One of the English language skills is reading. Reading is an activity in the cognitive process to get information in writing. Reading comprehension is a reading skill that is on a higher order. Reading comprehension is cognitive reading (reading to understand). There are many strategies for learning reading comprehension. One of them is the listen-read-discuss strategy. Listen-Read-Discuss (LRD) is a strategy that helps students build strong background knowledge to understand texts. The present study represents a meta-analysis of research results on the application of listening-reading-discussion strategies in reading comprehension. This meta-analytic study is a study that uses secondary data in the form of data from previous research findings. This research can be called follow-up research in the form of research reports and literature analyses. The tool of this research work is documentation, namely to obtain information about the application of the practice of listening-reading-discussing in reading comprehension. Data collection techniques were collected using a documentary technique. The technical data analysis used is descriptive, and to assess the sensitivity of the result of the so-called robust meta-analysis. From all 12 (twelve) studies, we can conclude that all studies show a good correlation with the listen/read/discuss (LRD) strategy in terms of reading comprehension. This means that LRD strategy helps learners to understand writing.